2010
DOI: 10.1111/j.1460-9592.2010.03484.x
|View full text |Cite
|
Sign up to set email alerts
|

Ketorolac tromethamine: stereo‐specific pharmacokinetics and single‐dose use in postoperative infants aged 2–6 months

Abstract: Objective-We determined the postoperative pharmacokinetics (PK), safety and analgesic effects of ketorolac in 14 infants (aged <6 months) receiving a single intravenous (IV) administration of racemic ketorolac or placebo.Background-Information on the PK of ketorolac in infants is limited. Unblinded studies suggest ketorolac may be useful in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 31 publications
4
39
0
Order By: Relevance
“…Others however have found no pain relief greater than placebo (Schoeler et al, ). When combined with other analgesics, ketorolac is reported by some to be as effective in reducing opiate use (Laudenbach et al, ; Yan et al, ) whereas other found no advantage adding NSAIDs to other analgesics (Enkvist et al, ; Brum et al, ; Lynn et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Others however have found no pain relief greater than placebo (Schoeler et al, ). When combined with other analgesics, ketorolac is reported by some to be as effective in reducing opiate use (Laudenbach et al, ; Yan et al, ) whereas other found no advantage adding NSAIDs to other analgesics (Enkvist et al, ; Brum et al, ; Lynn et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As in adults, ketorolac has been shown to provide effective postoperative pain relief in children, often decreasing opioid requirements. It is generally well tolerated, but the risk for bleeding and renal dysfunction must always be taken into consideration 24 . However, minimal safety data exist regarding the use of ketorolac in neonates 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Allegaert discusses the role of pharmacogenetics in tramadol CL (49). Major activity of a drug is often inherent in one stereoisomer; Lynne and colleagues present their work with ketorolac (50).…”
Section: Pediatric Anesthesia Pharmacologymentioning
confidence: 99%